Belajar Kosa Kata Bahasa Inggris Melalui Lagu Dengan Aktivitas Stereophonic Styrofoam: SD IT Nurul Fikri Palangka Raya - Abdul Syahid; Aulia Rahmi; Devi Hanas Tasya; Krisna Dwi Alifhia Rezky; Mirna Lestari; Meisya Rawenda; Nuralisa Nuralisa; Umi Maisarah; Wafa’ Qaulan Syahida (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The initiative "FUN ENGLISH LISTENING FOR KIDS" at SD IT Nurul Fikri aims to enhance the English language proficiency of young learners through innovative methods. This project utilizes stereophonic styrofoam to introduce and reinforce English vocabulary among elementary school students. Under the guidance of fifth-semester students from the English Language Teaching Program at IAIN Palangka Raya, the project involves stages of introducing vocabulary, using styrofoam to associate sounds with vocabulary, and interactive sessions. This engaging learning method has successfully improved the English skills of elementary students at SD IT Nurul Fikri, demonstrating the potential of creative methods in language education.